2012
DOI: 10.1037/a0028204
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, cognition, and behavioral problems in school-age children: A century of research meta-analyzed.

Abstract: Clear associations of sleep, cognitive performance, and behavioral problems have been demonstrated in meta-analyses of studies in adults. This meta-analysis is the first to systematically summarize all relevant studies reporting on sleep, cognition, and behavioral problems in healthy school-age children (5-12 years old) and incorporates 86 studies on 35,936 children. Sleep duration shows a significant positive relation with cognitive performance (r = .08, confidence interval [CI] [.06, .10]). Subsequent analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
435
5
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(473 citation statements)
references
References 221 publications
(301 reference statements)
21
435
5
12
Order By: Relevance
“…Importantly, the negative relation between sleep problems and academic functioning has been confirmed using both naturalistic and experimental studies (Astill et al 2012). For example, in an experimental sleep restriction study, Fallone et al (2005) found that restricted sleep resulted in significantly higher teacher ratings of academic problems.…”
Section: Academic Factorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Importantly, the negative relation between sleep problems and academic functioning has been confirmed using both naturalistic and experimental studies (Astill et al 2012). For example, in an experimental sleep restriction study, Fallone et al (2005) found that restricted sleep resulted in significantly higher teacher ratings of academic problems.…”
Section: Academic Factorsmentioning
confidence: 88%
“…Sleep and mental health functioning are clearly intertwined (see Astill et al 2012, for a meta-analytic review of schoolaged children), and, indeed, disturbed sleep is a symptom of several psychiatric disorders. Although sleep functioning is likely relevant to most, if not all, domains of mental health we limit the scope of our review herein to anxiety, depression, suicidal ideation/behaviors, externalizing behaviors, and substance use (attention problems are covered in more detail below in the section on ADHD).…”
Section: Mental Healthmentioning
confidence: 99%
“…Of note, a systematic review and metaanalysis concluded that insufficient sleep was associated with deficits in higher order and complex cognitive functions and with an increase in behavioral problems in children. 44 Participation in physical activity provides an opportunity for the development of self-regulation and coping skills that may influence mental health. For example, yoga is a holistic system of multiple mind-body practices for mental and physical health that includes relaxation practices, cultivation of awareness/mindfulness, and meditation 45 that help develop coping skills.…”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…This interest is derived from the results of recent studies that indicate that sleep regularity is important not only at structural and functional levels of the central nervous system but also at the behavioral level (Astill et al, 2012;Gruber et al, 2010). Although laboratory studies using experimental designs among children and adults have shown a negative effect of sleep deprivation on cognitive performance (Koslowsky & Babkoff, 1992;Lim & Dinges, 2010;Philibert, 2005;Pilcher & Huffcut, 1996), the way in which habitual sleep habits at school affect both academic and cognitive performance in adolescents and children in non-experimental conditions is still unclear (Dewald et al, 2010).…”
Section: Introductionmentioning
confidence: 99%